Hair Nicotine Levels in Children With Bronchopulmonary Dysplasia - Collaco, Joseph M. (Pediatrics, 2015)
BACKGROUND: Tobacco smoke exposure (TSE) may increase respiratory morbidities in young children with bronchopulmonary dysplasia (BPD). Rapid respiratory rates, close proximity to a smoking caregiver, and increased dermal absorption of tobacco smoke components can contribute to systemic exposure. In this study, hair nicotine levels were used as a biomarker of chronic TSE in young children with BPD to determine if hair nicotine levels correlate with caregiver self-report of TSE and respiratory morbidities. METHODS: From 2012 to 2014, hair nicotine levels were measured from consecutive children seen in a BPD outpatient clinic and compared with caregiver questionnaires on household smoking. The relationship between respiratory morbidities and self-reported TSE or hair nicotine level was assessed. RESULTS: The mean hair nicotine level from 117 children was 3.1 ± 13.2 ng/mg. Hair nicotine levels were significantly higher in children from smoking households by caregiver self-report compared with caregivers who reported no smoking (8.2 ± 19.7 ng/mg vs 1.8 ± 10.7; P < .001). In households that reported smoking, hair nicotine levels were higher in children with a primary caregiver who smoked compared with a primary caregiver who did not smoke. Among children with BPD who required respiratory support (n = 50), a significant association was found between higher log hair nicotine levels and increased hospitalizations and limitation of activity. CONCLUSIONS: Chronic TSE is common in children with BPD, with hair nicotine levels being more likely to detect TSE than caregiver self-report. Hair nicotine levels were also a better predictor of hospitalization and activity limitation in children with BPD who required respiratory support at outpatient presentation.